2000
DOI: 10.1007/s004420000442
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and life history responses of eastern massasauga rattlesnakes (Sistrurus catenatus catenatus) to human disturbance

Abstract: Parks and nature reserves protect important natural habitats but also provide public opportunities for outdoor recreational activities that may have unintended negative effects on wildlife. We examined the response of eastern massasauga rattlesnakes (Sistrurus catenatus catenatus) to inadvertent disturbance by humans in Killbear Provincial Park, Ontario, Canada. Radio telemetry of 25 adult snakes over two active seasons revealed that, as disturbance increased, gravid females were less visible to observers, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…It was seen that all the three species were distributed in all study locations, barring BWS, where T. malabaricus and H. hypnale were not recorded during the present study. This could be due to the anthropogenic activities in and around the sanctuary as human disturbances can affect the snakes in terms of their distribution (Greene 1988;Peterson 1990;Brown 1993;Parent & Weatherhead 2000). Terrestrial and arboreal habitats differ profoundly in many ways including the types and amount of food availability, vulnerability to predators, and physical factors such as temperature and humidity.…”
Section: Discussionmentioning
confidence: 99%
“…It was seen that all the three species were distributed in all study locations, barring BWS, where T. malabaricus and H. hypnale were not recorded during the present study. This could be due to the anthropogenic activities in and around the sanctuary as human disturbances can affect the snakes in terms of their distribution (Greene 1988;Peterson 1990;Brown 1993;Parent & Weatherhead 2000). Terrestrial and arboreal habitats differ profoundly in many ways including the types and amount of food availability, vulnerability to predators, and physical factors such as temperature and humidity.…”
Section: Discussionmentioning
confidence: 99%
“…Daily movement of snakes did not increase with cumulative road distance within their home range (F = 1.93, df = 1, 13, p = .19, Figure S4), but we had low power to detect an effect. Therefore, the predicted increase in annual energy expenditure represents 14% of the energy required to produce one neonate or 1% of a mean litter of 13 neonates (Parent & Weatherhead, 2000). Producing one neonate snake requires 65 kJ, assuming 6.75 kJ/g of snake (Dyke & Beaupre, 2011) and a mean neonate mass of 9.6 g (Jellen & Kowalski, 2007).…”
Section: Energetic Consequencesmentioning
confidence: 99%
“…Further, Parent and Weatherhead (2000) found that snakes continued to respond to people as if they were predators in disturbed areas, regardless of the level of disturbance. When an encounter situation occurs between a hatchling snake and a person, either the snake or the person detects the approach first.…”
Section: Discussionmentioning
confidence: 95%